A critical rewriting of global political economy : integrating reproductive, productive and virtual economies / V. Spike Peterson. - Peterson, V. Spike (RIPE series in global political economy, 2003)
Peterson rewrites global political economy by bringing disparate features of globalization into relation and providing an accessible narrative of 'how we got here', 'what is going on' and 'what it means' from a critical vantage point.